The Moderating Influence of External Environment on the Link Between Strategy Implementation Determinants and Public Health Facilities Service Delivery - Leonard, Momos (Journal of Indonesian Applied Economics, 2024)
Purpose This study aims to investigate the moderating influence of the external environment on the relationship between strategy implementation determinants and service delivery in public health facilities in the Western Region of Kenya. Design/methodology/approach The study adopts a positivist approach and is anchored on the McKinsey 7-S Model Framework. It utilizes descriptive survey and explanatory research designs, targeting 966 respondents including top management leaders, medical personnel, and patients. Data is collected through structured questionnaires and interview schedules, and analyzed using SPSS. Findings The external environment moderates the relationship between strategy implementation determinants and public health facilities service delivery in the Western Region of Kenya. Human resource capacity and organizational culture are key factors moderated by the external environment in affecting public health facilities service delivery. Research limitations/implications The study's findings are specific to the Western Region of Kenya and may not be generalizable to other regions or countries. The study relies on self-reported data, which may be subject to response bias. Originality/value This study contributes to the understanding of how the external environment influences the relationship between strategy implementation determinants and service delivery in public health facilities. The findings suggest the importance of creating an enabling environment for effective strategy implementation in the public sector to improve service delivery.